ANALISIS KEMAMPUAN INTELEKTUAL ANAK TUNAGRAHITA RINGAN DI SD NEGERI DEMAKIJO 2 - Avi Yanni; Izzatin Kamala; Muhammad Shaleh Assingkily; Rahmawati Rahmawati (LPPM Universitas Terbuka, 2020)
This study aims to determine (1) intellectual abilities of mentally retarded children in Demakijo State Elementary School (SD) 2 inclusive schools, (2) Obstacles faced by teachers when teaching at Demaijo State Elementary School 2, (3) Teachers' efforts in dealing with intellectual abilities of mentally retarded children in Demakijo State Elementary School 2. The type of approach used in this study is qualitative research with a survey method. Data collection techniques used were through observation and interviews with research subjects one mild retarded grade 1 student at Demakijo State Elementary School 2. The results of the intelligence test with the Wechsler Intelligence Scale For Children (WISC) obtained the results obtained scores of 57 Verbal IQ scores included in the IQ score of 57 Mental Retardation category. IQ Performance Score 55 included in the Mental Retardation category. With the total IQ obtained is 55 included in mental retardation. Based on the analysis results contained in the table in general, mild mental retardation children are difficult to manage and do not do the work. Efforts made by teachers when experiencing difficulties in understanding the lessons conveyed by children with mild mental retardation AD is to provide personal guidance, ask questions and answer, and several times be assertive. Penelitian ini bertujuan untuk mengetahui (1) kemampuan intelektual anak tunagrahita di sekolah inklusi Sekolah Dasar (SD) Negeri Demakijo 2, (2) Hambatan yang dihadapi guru ketika mengajar di SD Negeri Demaijo 2, (3) Upaya guru dalam menangani kemampuan intelektual anak tunagrahita di SD Negeri Demakijo 2. Jenis pendekatan yang digunakan dalam penelitian ini adalah penelitian kualitataif dengan metode penelitian adalah metode survei. Teknik pengumpulan data yang digunakanya itu melalui observasi dan wawancara dengan subjek penelitian satu anak tunagrahita ringan kelas 1 SD Negeri Demakijo 2. Hasil dari tes intelegensi dengan Wechsler Intelligence Scale For Children (WISC) mendapatkan hasil skor yang didapatkan yaitu skor IQ Verbal 57 yang termasuk dalam kategori Retardasi Mental. Skor IQ Performance 55 yang termasuk dalam kategori Retardasi Mental. Dengan jumlah IQ total yang didapatkanya itu 55 termasuk dalam Retardasi mental. Berdasarkan hasil analisis yang terdapat pada tabel secara umum anak tunagrahita ringan susah diatur dan tidak mengerjakan tugas. Upaya yang dilakukan guru ketika mengalami kesulitan dalam memahamkan pelajaran yang disampaikan anak tunagrahita ringan AD ialah dengan memberikan bimbingan pribadi, melakukan tanyajawab, serta beberapa kali bersikap tegas.